Pelatihan Soft Skill Problem Solving Pada Siswa SMK Dirgantara Riau - Elida Gultom; Lamin Lamin; Nova Syafrina; Jeli Nata Liyas (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This community service was carried out at SMK Dirgantara Riau which is located at Jalan Raya Pekanbaru-Bangkinang Tampan District, Pekanbaru City. This activity was carried out on Tuesday, April 18, 2023 with the theme Problem Solving Soft Skill Training for SMK Dirgantara Riau students. Students of SMK Dirgantara Riau are the next generation of the nation, at their young age they need to be equipped with knowledge about problem solving. How to identify problems to find solutions to the problems they face. This understanding of problem solving is very useful, both during the teaching and learning process and becomes an asset when working after graduating from school. The method of implementing this service was carried out in two ways, namely the lecture and training method. The results of this community service activity are expected to increase the understanding and skills of students of SMK Dirgantara Riau about problem solving so that they become strong, confident, critical and independent individuals.